Study of underwater communication channel for acoustic signals with OFDMA - Chai, Chin Leong (2010)
Underwater Acoustic Communications have witnessed a growing interest and increasing performance and complexity of signal processing systems over the last few decades. With applications in areas such as marine research, oceanography and military etc, the readily available high data rate acoustic communication systems has turned into a catalyst for an explosion of applications. However, efficient underwater acoustic communications are still hampered by several obstacles such as the presence of fading, multipath and refractive properties of the sound channel. Orthogonal Frequency Division Multiplexing (OFDM), a multi-carrier modulation technique that is fast becoming a popular scheme for wideband digital communications, due to its ability to cope with severe channel conditions such as attenuation and frequency selective fading, is being seen as a possible candidate for efficient underwater communications. Therefore, it is of research interest to investigate how OFDM can be applied and optimize the network capacity for such an environment.